2021
DOI: 10.1093/bjs/znab357
|View full text |Cite
|
Sign up to set email alerts
|

Radiological tumour invasion of splenic artery or vein in patients with pancreatic body or tail adenocarcinoma and effect on recurrence and survival

Abstract: Background Major vessel invasion is an important factor for determining the surgical approach and long-term prognosis for patients with pancreatic head cancer. However, clinical implications of vessel invasion have seldom been reported in pancreatic body or tail cancer. This study aimed to evaluate the clinical relevance of splenic vessel invasion with pancreatic body or tail cancer compared with no invasion and investigate prognostic factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Recently, ve studies suggested that radiological splenic vessel involvement can be a negative prognostic indicator. Among these, four studies found that radiological SpA involvement is a signi cant independent predictor of poor prognosis [7,8,10,11]. Additionally, two studies identi ed radiological SpV involvement as an independent poor prognostic factor [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ve studies suggested that radiological splenic vessel involvement can be a negative prognostic indicator. Among these, four studies found that radiological SpA involvement is a signi cant independent predictor of poor prognosis [7,8,10,11]. Additionally, two studies identi ed radiological SpV involvement as an independent poor prognostic factor [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, in pancreatic body or tail cancer, the involvement of these vessels is not surgically signi cant but is a poor prognostic factor in oncology, along with lymph node metastasis, tumour size, and tumour differentiation [4][5][6]. Although there have been several studies on splenic vessel involvement [5,[7][8][9], especially on SpA involvement [10][11][12][13][14], few studies have focused on SpV involvement [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies reported that pathological infiltration of SV is associated with a worse prognosis ( 31 - 33 ), resectable left-sided PDAC with SVs invasion alone is considered “anatomically” resectable disease. However, recent studies reported that radiologic SVs invasion is associated with a poor prognosis, suggesting a need for NAT ( 34 - 36 ). The present study also showed a poor prognostic impact of radiologic SVs invasion in anatomically resectable left-sided PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer is a deadly malignancy around the world according to the latest global reports [1,2] and is expected to be the second leading cause of cancer-related death in 2030 [2]. Surgery [3], radiotherapy [4], chemotherapy [5,6], and immunotherapy [7,8] are available for pancreatic cancer treatment; however, recurrence and metastasis occur [9][10][11][12][13][14][15] frequently after treatment [16]. Therefore, the identification of additional molecular targets and development of novel therapeutic strategies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%